Novel approaches to enable equitable access to monoclonal antibodies in low- and middle-income countries. - Shelly Malhotra; Anne-Isabelle Cameron; Dzintars Gotham; Esteban Burrone; Peter J Gardner; Colleen Loynachan; Sébastien Morin; Cherise P Scott; Carmen Pérez-Casas (PLOS Global Public Health)
Monoclonal antibodies (mAbs) are revolutionizing management of non-communicable diseases in high-income countries and are increasingly being advanced for a range of infectious diseases (IDs). However, access to existing mAbs is limited in low- and middle-income countries (LMICs), and investment in developing fit-for-purpose mAbs for IDs that disproportionately affect LMICs has been limited. Underlying these access barriers are systemic challenges, including a lack of commercial incentives to target LMIC markets and complexity in manufacturing and regulatory processes. Novel strategies are needed to overcome systemic access barriers for mAbs. We outline key areas where new approaches could address these barriers, based on a multistakeholder consultation in March 2023. Three disease-market archetypes are identified to guide thinking about business models tailored to different contexts. New business models are needed to incentivize development and manufacturing of ID mAbs and to ensure mAbs are optimized with a target product profile and cost of goods that enable use in diverse LMIC settings. Lessons can be applied from voluntary licensing strategies and product development partnerships that have shown success in catalysing development and affordable supply for a range of infectious diseases. Technology transfer will be key to expand LMIC research and manufacturing capacity and to enable sustainable and diversified supply. Improved market intelligence, demand aggregation mechanisms, and portfolio-based manufacturing models could be used to de-risk commercial investment and establish a sustainable manufacturing ecosystem for affordable mAbs. Novel regulatory approaches and robust technology transfer may reduce data requirements and timelines for biosimilar approvals. Trailblazer products, with coordinated "end-to-end" support from funders, can demonstrate proof of concept for pathways to accessible mAbs across a broader range of LMICs. Research funders; local, regional, global health agencies; and, private sector partners should commit to implementing innovative partnerships and end-to-end strategies that enable equitable access to mAbs for infectious diseases in LMICs.